Oil wastes as unconventional substrates for rhamnolipid biosurfactant production by Pseudomonas aeruginosa LBI - Nitschke, Marcia [UNESP]; Costa, Siddhartha G. V. A. O. [UNESP]; Haddad, Renato; Gonçalves, Lireny A. G.; Eberlin, Marcos N.; Contiero, Jonas [UNESP] (Wiley, 2005)
Oil wastes were evaluated as alternative low-cost substrates for the production of rhamnolipids by Pseudomonas aeruginosa LBI strain. Wastes obtained from soybean, cottonseed, babassu, palm, and corn oil refinery were tested. The soybean soapstock waste was the best substrate, generating 11.7 g/L of rhamnolipids with a surface tension of 26.9 mN/m, a critical micelle concentration of 51.5 mg/L, and a production yield of 75%. The monorhamnolipid RhaC10C10 predominates when P. aeruginosa LBI was cultivated on hydrophobic substrates, whereas hydrophilic carbon sources form the dirhamnolipid Rha2C10C10 predominantly. © 2005 American Chemical Society and American Institute of Chemical Engineers.
Keywords: Biomaterials; Carbon; Critical micelle concentration; Hydrophobicity; Lipids; Plants (botany); Substrates; Surface active agents; Surface tension; Biosurfactants; Oil wastes; Production yields; Rhamnolipids; Wastes; glycolipid; rhamnolipid; surfactant; vegetable oil; biotransformation; chemistry; industrial waste; isolation and purification; metabolism; Pseudomonas aeruginosa; Biotransformation; Glycolipids; Industrial Waste; Plant Oils; Surface-Active Agents; Glycine max; Micropus; Orbignya barbosiana; Zea mays